Action Score Generator (2014). (1st September 2016) - Walker, Nathan
The Action Score Generator is an online writing machine that writes and re-writes an infinite series of performance event scores. The source texts collect together previously performed actions by artist Nathan Walker between 2006 and 2013. The scores are arranged into poetic, six-word-length instructions, aligning performance objects, tasks, verbs and spaces that are reorganized endlessly by a JavaScript code. The Action Score Generator aligns itself with the short poetic texts of Fluxus Event Scores and with rhythms of computational data and visual poetry. An Action Score Generator book is published by IF P THEN Q Press, Manchester, including an Afterword by Mark Leahy entitled 'An action movie (for NW): Reading time code action'.